The Role of Indonesian Medical Council in Assuring The Quality of Medical Education - Titi Savitri Prihatiningsih (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: Indonesian Medical Council (IMC) was established in October 2005 as mandated by the Medical Practice Law No.29/2004. The main function of IMC is to safeguard the medical practices through several mechanism, one of which is through ensuring the quality of medical education by approving the standards of competences and standards of medical education as well as by monitoring the implementation of those standards. A new Medical Education Law No.20/2013 is enacted. In this Law, the role of IMC in assuring the quality of  medical education disappeared.Method: This is an exploratory qualitative study. Documents are analysed using a content analysis. Typology for medical regulatory framework is applied.Results: Five categories are identified, namely (1) educationally-oriented regulators, (ii) mix regulatory regimes, (iii) collaborative governance, (iv) professional regulation and (v) mix-credentialing regimesConclusion: For governance of medical education, educationally-oriented regulators predominates. In quality assurance for medical education, mix-regulatory, collaborative governance and professional regulation are applied; however there is a contradictory of role between IMC and the Ministry. In funding, mix-regulatory regime and collaborative regime are applied. In education trajectory, educationally-oriented regulator is used and in exam and qualification mix-credentialing regime is applied. Only in quality assurance in medical education, there is a serious contradiction of IMC role.